Analysis of Prospective Mathematics Teachers Difficulties on Learning Calculus - Sri Ulfah Afriani; Andi Mangaraja; Rama Nida Siregar (IKIP Siliwangi, 2026)
Calculus is a fundamental subject in mathematics education, yet it poses significant challenges for students, particularly prospective mathematics teachers. This study aims to analyze the difficulties faced by seventh-semester mathematics education students at the South Tapanuli Institute of Education in learning calculus, focusing on both cognitive and affective factors. Using a descriptive qualitative approach, data were collected via an online questionnaire distributed to five students who had completed a calculus course. The questionnaire investigated conceptual, procedural, and representational difficulties, as well as factors such as anxiety and inadequate academic support. The results revealed that students struggled most with conceptual understanding, particularly in limits, derivatives, and integrals, and with applying calculus rules in problem-solving. Representation difficulties were also noted, especially in connecting algebraic expressions with graphical interpretations. Contributing factors included insufficient mastery of prerequisite mathematical concepts, limited exposure to visual learning tools, and high levels of anxiety related to calculus. The study concludes that students’ difficulties are not merely the result of the inherent complexity of calculus, but are also influenced by cognitive and emotional barriers. Recommendations include the integration of visual media and interactive tools, alongside improved instructional strategies and support systems to enhance students' conceptual understanding and reduce anxiety. The findings contribute to the development of more effective calculus teaching strategies in teacher education.